2006
DOI: 10.1002/humu.20267
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the interaction between twoADAMTS13 gene mutations leading to severe deficiency of enzymatic activity

Abstract: The inherited deficiency of the von Willebrand factor-cleaving protease ADAMTS13 is associated with rare forms of thrombotic thrombocytopenic purpura (TTP). We investigated a woman with a family history of chronic recurrent TTP and undetectable plasma levels of ADAMTS13 activity. Genetic analysis revealed two missense mutations in the heterozygous state: p.Val88Met substitution in the metalloprotease domain and p.Gly1239Val substitution in the first CUB domain of ADAMTS13. To explore the mechanism of ADAMTS13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
2
34
1
Order By: Relevance
“…Multimeric analysis of VWF The multimeric pattern of plasma VWF was analyzed by sodium dodecyl sulfate agarose gel electrophoresis followed by luminographic visualization of multimers [10]. EDTA plasma samples were diluted in order to obtain final VWF:Ag concentrations of 10%.…”
Section: Study Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimeric analysis of VWF The multimeric pattern of plasma VWF was analyzed by sodium dodecyl sulfate agarose gel electrophoresis followed by luminographic visualization of multimers [10]. EDTA plasma samples were diluted in order to obtain final VWF:Ag concentrations of 10%.…”
Section: Study Measurementsmentioning
confidence: 99%
“…Densitometric analysis was performed on the blotted membrane using the graph line obtained by the single lane of the gel and plasma samples with similar VWF concentrations in order to obtain comparable area values. According to Budde and Scheneppenheim [11], the reference plasma lane was divided into small (1-5), intermediate (6)(7)(8)(9)(10) and larger (> 10) multimers of regular size. The proportion of larger multimers in the sample was calculated by dividing the area corresponding to larger multimers by the total area of the lane.…”
Section: Vwf-related Measurements In Ttp 1745mentioning
confidence: 99%
“…Immunofluorescence experiments were performed as previously reported. 17 To detect the cellular localization of WT and mutant ADAMTS13 recombinant proteins, transfected cells were stained simultaneously with anti-V5 antibody and mouse monoclonal antibodies against the protein Bip-GRP78 (a chaperone protein involved in Golgi-endoplasmic reticulum transport) (BD Biosciences, Franklin Lakes, NJ, USA). Images were captured using a Leica DMR epifluorescence microscope (Leica Imaging System, Cambridge, UK) equipped with a CCD camera (Cohu, San Diego, CA, USA) and a specific filter.…”
Section: Immunofluorescence Studiesmentioning
confidence: 99%
“…[15][16][17][18][19] The present study evaluates the molecular mechanism of two mutations observed in the compound heterozygous state in two Turkish siblings with congenital TTP. One mutation, present on the maternal allele, is a single base (A) insertion mutation located within exon 29 (c.4143_4144insA) in the second CUB domain, leading to a frameshift and loss of the last 49 amino acids of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme consists, from the N-terminus, of a relatively short propeptide, the catalytic site, the disintegrin-like (DLD), a first thrombospondin-1 (TSP1) repeat, the Cys-rich domain, the spacer domain, seven TSP1 repeats and 2 CUB (complement components C1r/C1s, urinary Epidermal Growth factor and bone morphogenetic protein-1) domains at the C-terminus (6), whose free thiols have also direct antithrombotic effects (7). When there is a deficiency of this enzyme, uncleaved, ultra large VWF multimers accumulate in microcirculation, causing increased platelet adhesion and aggregation, resulting in the formation of VWF-and platelet-rich thrombi (1,8,9). The development of microthrombi results in microangiopathic haemolytic anaemia and causes variable symptoms of organ ischemia and dysfunction (1).…”
Section: Introductionmentioning
confidence: 99%